Peningkatan Kemampuan Promosi Produk Melalui Konten Kreatif di Media Sosial bagi Siswa-Siswi di SMAN 1 Maja - Asri Nabila Jahro; Ade Ridwan; Maulana Maulana; Sabila Al Zahra; Lailatul Qomariyah (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This community service activity aims to improve students’ ability to promote products through the creation of creative content on social media among students of SMAN 1 Maja. In today’s digital era, the use of social media as a marketing tool has become increasingly important, especially for the younger generation who have great potential to develop creativity and an entrepreneurial mindset. However, many students still lack adequate knowledge and skills in creating effective and engaging promotional content. The implementation methods of this activity include the provision of materials, training sessions, and direct assistance in creating creative content, such as product photography, promotional videos, and persuasive caption writing. In addition, participants will also be introduced to basic digital marketing strategies, the use of social media algorithms, and simple branding techniques. The expected outcome of this activity is an improvement in students’ understanding and skills in utilizing social media as a means of product promotion.